PROMOSI KESEHATAN SANITASI PERORANGAN PADA KEJADIAN PENYAKIT KULIT MELALUI PENYULUHAN PADA MASYARAKAT DUSUN II DESA NAMO TUALANG KECAMATAN BIRU-BIRU KABUPATEN DELI SERDANG - Novrika Silalahi; Muhraza Siddiq; Tedty Rohaya Tinambunan; Sulastri Br Ginting; Armanda Prima (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
This counseling aims to identify and develop alternative solutions to health problems in the community, by increasing knowledge about 5 disease problems namely ARI, diarrhea, hypertension, diabetes mellitus and skin diseases by providing health education counseling. The problem priority method for counseling is using the CARL method (capability, accessibility, readiness, and leverage), so that the biggest disease problem is skin disease due to lack of public knowledge about skin hygiene, hand hygiene, nail and towel hygiene and with the aim of reducing sufferers. skin diseases and improve health status in Hamlet II, Namo Tualang Village, Bitu-Biru District.